PHYSIOTHERAPY MANAGEMENT IN POST ACL RECONTUTION USING CLOSE KINETIC CHAIN EXERCISE IN PHASE III: A CASE REPORT - Widodo, Faressa; Wijianto, W; Mardianto, Halim (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: One of the ligaments in the knee is the anterior cruciate ligament where the function of the ligament itself is joint stabilization. 60% sports injuries occur in the knee, one of which is specifically a tear in the anterior cruciate ligament (ACL) ligament with the largest incidence rate of 16% during sports activities then the role of physiotherapy using close chain kinetic is expected to overcome pain, increase range of motion, reduce muscle atrophy and increase muscle strength. Case Presentation: A 23-year-old man last year had an accident while playing soccer and the patient felt the instability of his right knee when he was running, then after an MRI was done at the hospital 6 months ago the patient had ruptured anterior cruciate ligament ligament (ACL) so 3 months ago it was done post anterior cruciate ligament (ACL) reconstruction measures. Management and Outcomes: Giving therapy Exercises such as close chain exercise are effective for reducing pain, increasing muscle strength around the knee joint, reducing atrophy in the muscles around the knee joint as measured by the medline. Discussion: After doing physiotherapy rehabilitation for 6 times therapy, the pain reduction from the first therapy was worth 3 then the last therapy was 2 measured by NRS (numeric rating scale), then the range of motion increased by 5o from before exercise measured with a goneometer, for anthropometry it increased by 0.5 cm to 2 cm and muscle strength was stable at 5. Conclusion: After 2 weeks of therapy for 6 x sessions with intervention of close chain kinetic exercise therapy, the results were decreased pain, increased range of motion, increased muscle strength, reduced repeated falls, and reduced atrophy in the muscles that work on the knee joint.